Whether vitamin D(3) is effective in reducing proteinuria in type 2 diabetic patients? - Ahmadi, Nooshin (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Nowadays Vitamin D deficiency is a notable medical condition world-wide and also in Iran. Since, vitamin D can have renoprotective effect by inhibiting the renin-angiotensin system; it appears that low vitamin D level can worsen the renal injury in diabetic patients. This study demonstrates the effect of vitamin D(3) therapy on reducing proteinuria in diabetic patients with concomitant diabetic nephropathy and vitamin D deficiency after controlling hypertension and use of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin II type receptor blockers (ARBs). MATERIALS AND METHODS: In this randomized double blinded parallel groups clinical trial, 51 diabetic patients with proven nephropathy and vitamin D deficiency/insufficiency and stable hypertension, dyslipidemia, and hyperglycemic treatment were enrolled. The patients were divided randomly into two groups (treatment and placebo group). Patients received oral vitamin D(3) (pearl 50000 IU) or placebo one pearl every week for 12 weeks. Patients were assessed at baseline and 12 weeks after intervention from the point of 25(OH) D level, and urine albumin/creatinine ration (UACR). RESULTS: Mean serum 25(OH) D concentrations were 14.06 ng/ml and 16.05 ng/ml before treatment. Furthermore, after intervention, its levels were risen to 71.23 and 17.63 in drug and placebo groups, respectively. Whereas, UACR as the main variable did not change significantly after intervention in both groups (P = 0.919). CONCLUSION: According to our finding, there was not a decrease in proteinuria in diabetic patients who received vitamin D for a period of 3 months.